Students’ statistical literacy on junior high school - N Mulya; E Nurlaelah; S Prabawanto (International Conference on Mathematics and Science Education of Universitas Pendidikan Indonesia, 2018)
Statistical literacy is a key ability expected of citizens in information-laden societies, and is often touted as an expected outcome of schooling and as a necessary component of students' numeracy and literacy. The facts show that the statistical literacy ability of Indonesian students is still in an alarming category and Indonesian students for junior high school have not been able to compete internationally in the statistical literacy. This qualitative descriptive research was conducted to describe junior high school students’ ability and difficulties in basic skills of statistical literacy. Data were collected from 6 students of 8th grade in one of junior high school in Aceh, Indonesia through test and interviews. The results clearly show that students’ statistical literacy are still in low category. Students are good in understanding the data but they have limited understanding of the data presentation concept. Students have difficulty in using the principle of presenting the data into the pie chart. Many steps of presenting the data are not complete. From this study can be concluded that students’ basic skills of statisical literacy has not been satisfied. Therefore, mathematics learning process in data presentation concept should be improved.